Population Genetic Structure and Genetic Diversity in Twisted-Jaw Fish, Belodontichthys truncatus Kottelat & Ng, 1999 (Siluriformes: Siluridae), from Mekong Basin - Surapon Yodsiri; Komgrit Wongpakam; Adisak Ardharn; Chadaporn Senakun; Sutthira Khumkratok (International Journal of Zoology)
The Mekong River and its tributaries possess the second highest diversity in fish species in the world. However, the fish biodiversity in this river is threatened by several human activities, such as hydropower plant construction. Understanding the genetic diversity and genetic structure of the species is important for natural resource management. Belodontichthys truncatus Kottelat & Ng is endemic to the Mekong River basin and is an important food source for people in this area. In this study, the genetic diversity, genetic structure, and demographic history of the twisted-jaw fish, B. truncatus, were investigated using mitochondrial cytochrome b gene sequences. A total of 124 fish specimens were collected from 10 locations in the Mekong and its tributaries. Relatively high genetic diversity was found in populations of B. truncatus compared to other catfish species in the Mekong River. The genetic structure analysis revealed that a population from the Chi River in Thailand was genetically significantly different from other populations, which is possibly due to the effect of genetic drift. Demographic history analysis indicated that B. truncatus has undergone recent demographic expansion dating back to the end of the Pleistocene glaciation.